Physics Learning Using Brainly Platform During Pandemic in Mataram City - Thufail Mujaddid Al-Qoyyim; Johana Aulina Rahmatin; Barinta Nur Respasari; Hijrotussulusi Hijrotussulusi; Muhammad Zuhdi; Aris Doyan (Pascasarjana, Mataram University, 2023)
The COVID-19 pandemic has had an impact on the implementation of education, including learning physics. All learning processes must be carried out online to stop the spread of the virus. Online physics learning is physics learning that is carried out in a network by utilizing technological advances in the form of the internet to achieve learning objectives. There are various means of supporting online learning. Technological advances are so rapid, making it easier for students to get learning resources that are relevant to curriculum needs. One of the most popular online learning resources is Brainly. Brainly is quite popular among students and teachers and is often used to support learning, especially online learning of physics. The purpose of this study was to find out how the use and impact of Brainly in learning physics. The method used in this research is descriptive qualitative with a questionnaire instrument distributed to high school students in Mataram City through WhatsApp Groups. It was found that the use of Brainly in physics learning is quite often used and has a positive impact on student learning outcomes